Enhanced conductivity of hole transport layers via nickel oxide and graphenated-carbon nanotube (G-CNT) composites - Shafie, Suhaidi; Norddin, Nurbahirah; Hamidon, Mohd Nizar; Liu, Xinzhi; Idris, Muhammad Idzdihar; Ahmad, Fauzan (Universiti Putra Malaysia, 2024)
Perovskite solar cells represent a highly promising renewable energy technology due to their exceptional efficiency and cost-effectiveness. However, limitations exist in commonly used hole transport layers (HTLs) like Spiro-OMeTAD and PEDOT: PSS, which have their drawbacks. Nickel oxide (NiO) is a potential alternative HTL material but suffers from high resistivity which involves low carrier concentration, defect density,and poor charge mobility. In this study, the influence of a graphenated carbon nanotube (g-CNT) mixture on the physical, electrical, and surface morphological properties of NiO thin films was investigated. NiO:g-CNT were synthesized using a sol-gel method and characterized by field emission scanning electron microscopy (FESEM) to analyze surface morphology, X-ray diffraction (XRD) for structural properties, and energy-dispersive X-ray spectroscopy (EDX) for elemental analysis. Electrical properties were measured using a four-point probe to assess conductivity. The results revealed that incorporating 0.5 wt% g-CNT into NiO significantly reduced the resistance of the thin films from 255 kΩ to 67 kΩ. This improvement is attributed to the g-CNT’s ability to bridge grain boundaries, enhancing charge transport, even though the crystallite size was smaller compared to pristine NiO. These findings suggest that NiO could improve the performance of perovskite solar cells by enhancing their conductivity.